An Analysis of Security Market Growth and Individuals' Investment Decision - Joshi, Dipika (Journal of Business and Social Sciences Research, 2019)
The purpose of this study is to analyze the growth of Security Market from FY2005/06 to FY 2016/17 and to determine the most influencing factor that drive investment decision. The security market growth indicators taken are Market Size and Market Liquidity. To examine the relationship between Investment Decision and influencing factors, factors such as Advocate Recommendation, Personal Financial Needs, Accounting Information, Firm’s Image and Neutral Information are taken into consideration. For this study, data are collected both from primary as well as secondary sources. To analyze the growth of stock market, secondary data have been obtained from annual publication of NEPSE, SEBON, MOF etchant statistical analysis like Ratio Analysis (such as MCR and ML), Growth Analysis and Correlation have been applied. For the study of investment decision, primary data have been collected with the sample size of 200. T-test has been applied to examine the relationship between investment decision and influencing factors. The result shows that Nepalese capital market has erratic trend during study period. It implies that capital market is immature and investors are not motivated to invest in the companies. It is also not deniable that the capital market has developed compared to FY 2005/06. Furthermore, Nepalese investors mostly consider firm’s reputation in the industry and opinion of firms’ majority of stockholder before investing in any stock.